2017
DOI: 10.1073/pnas.1705551114
|View full text |Cite
|
Sign up to set email alerts
|

A distinct subpopulation of CD25T-follicular regulatory cells localizes in the germinal centers

Abstract: T-follicular helper (Tfh) cells differentiate through a multistep process, culminating in germinal center (GC) localized GC-Tfh cells that provide support to GC-B cells. T-follicular regulatory (Tfr) cells have critical roles in the control of Tfh cells and GC formation. Although Tfh-cell differentiation is inhibited by IL-2, regulatory T (Treg) cell differentiation and survival depend on it. Here, we describe a CD25− subpopulation within both murine and human PD1+CXCR5+Foxp3+ Tfr cells. It is preferentially l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
236
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 174 publications
(261 citation statements)
references
References 56 publications
13
236
3
Order By: Relevance
“…35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs. 35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs.…”
Section: Cd25/il-2 Axis In Tfr-cell Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs. 35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs.…”
Section: Cd25/il-2 Axis In Tfr-cell Responsesmentioning
confidence: 99%
“…35,69,70 Wing and colleagues showed that following immunization both CD25 − and CD25 + Tfr cells emerge with the CD25 − Tfr cells preferentially locating within GCs. 69 Moreover, CD25 − Tfr cells presented a gene expression profile more similar to the one of Tfh cells. 69 In tissue sections, there was a greater number of CD25 -Foxp3 + T cells within GC, although some CD25 + Foxp3 + T cells could also be found.…”
Section: Cd25/il-2 Axis In Tfr-cell Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA expression of murine Tfr cells measured as Fragments Per Kilobase Million (FPKM) taken from RNAseq dataset in Wing et al (26). n = 2 ±SEM.…”
Section: Mechanisms Of Tfr Functionmentioning
confidence: 99%
“…The clustering together of TFH-like cells and FoxP3 + Helios + regulatory T cells further raises the possibility that T follicular regulatory cells are also present 43,44 . A distinct set of effector CD4 + T cells could be …”
Section: Cc-by-nc-nd 40 International Licensementioning
confidence: 99%